PENGARUH KEPEMILIKAN SAHAM, KINERJA KEUANGAN,DAN UKURAN PERUSAHAAN TERHADAP PENGUNGKAPANCORPORATE SOCIAL RESPONSIBILITY(Studi Empiris pada Perusahaan Manufaktur yang Terdaftar (listing) di BEItahun 2012-2014) - Kurniyawati, Indah, Dr. Triyono, S.E., M.Si (2016)
This study is aimed to examine the effect of foreign shareholding, Ppublic shareholding, leverage, profitability, and firm size on the disclosure of corporate social responsibility. The population used companies listed in Indonesian Stock Exchange during the years 2012-2014. This research is using purposive sampling technique. Analysis technique used is multiple regression analysis. The result of this study shows that: (1) firm size has an influence on the corporate social responsibility disclosure (2) foreign shareholding has no effect on the the corporate social responsibility disclosure, (3) public shareholding has no effect on the the corporate social responsibility disclosure, (4) leverage has no effect on the the corporate social responsibility disclosure, and (5) profitability has no effect on the the corporate social responsibility disclosure.